Low Long Noncoding RNA Growth Arrest-Specific Transcript 5 Expression in the Exosomes of Lung Cancer Cells Promotes Tumor Angiogenesis. (2nd May 2019) - Cheng, Ying; Dai, Xin; Yang, Ti; Zhang, Nan; Liu, Zhenzhong; Jiang, Yiguo
Abstract : Angiogenesis plays a key role in the development and progression of lung cancer. Recent studies have found that tumor cells can stimulate angiogenesis by secreting exosomes, which contain many long noncoding RNAs (lncRNAs), some of which are important for the development of lung cancer. However, the roles and mechanisms of exosomal lncRNAs in lung cancer angiogenesis have not yet been reported. In this study, lung cancer in mice was induced by urethane; we found that growth arrest specific 5 (GAS5) was lowly expressed in the serum exosomes and lung cancer tissues of mice with lung cancer. And there was a significant positive correlation between GAS5 expression in serum exosomes and lung cancer tissues. Furthermore, GAS5 was lowly expressed in human lung cancer tissues, lung cancer cells, and cells culture supernatant exosomes. The exosomes of lung cancer cells promoted human umbilical vein endothelial cells (HUVECs) proliferation and tube formation and inhibited their apoptosis. GAS5 overexpression in lung cancer cells increased GAS5 level in cell culture supernatant exosomes. And the exosomes of lung cancer cells containing high GAS5 level inhibited HUVECs proliferation and tube formation and increased their apoptosis. In addition, we found that GAS5 competitively bound miRNA-29-3p with phosphatase and tensin homolog (PTEN), upregulating PTEN mRNA and protein expression, and inhibited level of phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit alpha (PI3K) and serine/threonine kinase 1 (AKT) phosphorylation in HUVECs. Overall, our results suggest that exosomal GAS5 could be a new therapeutic target for lung cancer which inhibits angiogenesis.